2018
DOI: 10.1038/s41598-018-33525-5
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin loss induces targetable autocrine activation of growth factor signalling in lobular breast cancer

Abstract: Despite the fact that loss of E-cadherin is causal to the development and progression of invasive lobular carcinoma (ILC), options to treat this major breast cancer subtype are limited if tumours develop resistance to anti-oestrogen treatment regimens. This study aimed to identify clinically targetable pathways that are aberrantly active downstream of E-cadherin loss in ILC. Using a combination of reverse-phase protein array (RPPA) analyses, mRNA sequencing, conditioned medium growth assays and CRISPR/Cas9-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 54 publications
12
68
0
Order By: Relevance
“…This is consistent with other reports demonstrating that E-cadherin-mediated adhesion negatively regulates IGF1R activation [37,38]. Furthermore, in breast cancer models, loss of E-cadherin and the subsequent activation of IGF1R signaling results in increased sensitivity to dual IGF1R/Insulin receptor inhibitors, and Akt inhibitors that target downstream receptor pathway activation, even in the presence of activating PIK3CA mutations [36,37]. Interestingly, increased expression of IGF1 is seen in ILC compared to IDC [27,36,39], consistent with reported pathway activation [36,37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with other reports demonstrating that E-cadherin-mediated adhesion negatively regulates IGF1R activation [37,38]. Furthermore, in breast cancer models, loss of E-cadherin and the subsequent activation of IGF1R signaling results in increased sensitivity to dual IGF1R/Insulin receptor inhibitors, and Akt inhibitors that target downstream receptor pathway activation, even in the presence of activating PIK3CA mutations [36,37]. Interestingly, increased expression of IGF1 is seen in ILC compared to IDC [27,36,39], consistent with reported pathway activation [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…Previously we have shown that loss of E-cadherin promotes hypersensitization of PI3K/Akt pathway activation in response to IGF1, independent of PAPP-A [36], as well as oncogenic mutations in the PI3K/Akt pathway that are prevalent in ILC [5]. This is consistent with other reports demonstrating that E-cadherin-mediated adhesion negatively regulates IGF1R activation [37,38].…”
Section: Discussionsupporting
confidence: 92%
“…ILC is the 6 th most common cancer in women, with an estimated 40,000 new cases in 2019, despite accounting for a smaller proportion of breast cancer cases (~15%) compared to IDC (~75%) 1 . ILC shows distinct signaling in pathways essential for breast cancer growth and proliferation compared to IDCsuch as the WNT4 signaling in response to estrogen stimulus or blockade 2,3 , increased PI3K/Akt signaling 4,5 , enhanced IGF1-IGF1R activation 6 , and dependency on ROS1 7 , which suggest that ILC could benefit from unique treatment strategies. The most distinguishing molecular feature of ILC is loss of E-cadherin, largely arising from inactivating CDH1 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, WNT4 in ILC may represent an alternative pathway for the activation of mTOR signaling, potentially in concert with estrogen regulation of WNT4 and low PTEN, as high WNT4-expressing ILC also had decreased phospho-Akt (Supplemental Figure 7E). A recent study by Teo et al linked Akt activation to loss of Ecadherin (the hallmark feature of ILC [4]), but these studies identified this link using ER-negative ILC models (murine p53/CDH1-null lines and IPH-926) [50]. These observations suggest that even within ILC, subsets with distinct modes of PI3K/Akt/mTOR signaling exist.…”
Section: Discussionmentioning
confidence: 99%